Infectious keratoconjunctivitis in semi-domesticated reindeer (Rangifer tarandus tarandus): a questionnaire-based study among reindeer herders in Norway and Sweden - Wallin Philippot, Karin; Baron, Jerome; Sánchez Romano, Javier; Rautiainen, Heidi; Frössling, Jenny; Nymo, Ingebjørg Helena; Persson, Ylva; Omazic, Anna; Tryland, Morten (Acta veterinaria Scandinavica, 2023)
The effects of climate change, loss of pastureland to other land usage and presence of large carnivores are the main reasons for the increase in supplementary feeding of semi-domesticated reindeer (Rangifer tarandus tarandus) in Fennoscandia over the last decades. Feeding might expose reindeer to stress and increased animal-to-animal contact, leading to an increased risk of infectious disease transmission, such as infectious keratoconjunctivitis (IKC). As it can develop rapidly and be very painful, IKC is described as an important animal welfare concern and a potential source of economic loss. The aim of this study was to investigate the current presence of IKC and potential associations between IKC and supplementary feeding through an online questionnaire survey, distributed among reindeer herders in Norway and Sweden in 2021.